1980
DOI: 10.1017/s001447970001084x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Carriers on Seedling Establishment after Fluid Drilling

Abstract: S U M M A R Y Six products possessing suitable physical properties as fluid carriers for pre-germinated seed were assessed for their effects on seedling emergence. Both glasshouse and field experiments measured the carriers' performance on eight crop species at varying extrusion rates and under different environmental conditions. Synthetic clay or polyacrylate increased seedling emergence by 10% compared with the sodium alginate control. Seedling emergence was least affected by moisture stress when synthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Ross and Hegarty (1979) (Table 2) whereas percent FC had a significant affect among the dry seeded treatments. These results also suggest the possibility of the gel supplying some moisture to the developing seedling as reported by Elliott (1976 Gray (1978) and Darby (1980) Brocklehurst (1979) suggested that decreases in seeding emergence of fluid drilled treatments could result from limited oxygen availability to the seed, especially under wet soil conditions. Under the conditions of this experiment, the lower emergence levels could be related to reduced oxygen availability or at least related to some physical impediment imposed by the gel.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Ross and Hegarty (1979) (Table 2) whereas percent FC had a significant affect among the dry seeded treatments. These results also suggest the possibility of the gel supplying some moisture to the developing seedling as reported by Elliott (1976 Gray (1978) and Darby (1980) Brocklehurst (1979) suggested that decreases in seeding emergence of fluid drilled treatments could result from limited oxygen availability to the seed, especially under wet soil conditions. Under the conditions of this experiment, the lower emergence levels could be related to reduced oxygen availability or at least related to some physical impediment imposed by the gel.…”
supporting
confidence: 69%
“…Sowing pregerminated lettuce seed using the fluid drilling tech-nique has alleviated problems associated with seedling emergence at low (FinchSavage 1981) and high (Gray 1977;Darby 1980) soil temperatures and has improved seedling emergence when soil moisture was limited (Gray 1978). Earlier and more uniform emergence with fluid drilling compared to dry seeding has resulted in increased weight and uniformity of lettuce heads at harvest (Hemphill 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elliot (1967) was the first to use the technique experimentally and suggested that the gel provided water to the developing seedling. Under very dry soil conditions, some gels may actually dry out and trap the seedlings (Darby, 1980). Under very dry soil conditions, some gels may actually dry out and trap the seedlings (Darby, 1980).…”
Section: Fluid Drillingmentioning
confidence: 99%
“…There were 12 seed and covering-medium treatments involving all combinations of three types of seeds: 'splitkote' pellets, natural and pre-germinated seeds from the same seed lot of the variety Pennlake, and four covering media: frame soil, 2-5% Laponite (a synthetic mineral clay gel used for fluid drilling (Darby, 1980)), Grade 3 vermiculite and a 50:50 (by volume) sedge peat-vermiculite mixture. The Laponite concentration (2-5%) was greater than that normally used for fluid drilling (1-5%) in order to retain gel structure when surface-sown.…”
Section: Experiments 1 1980mentioning
confidence: 99%